3XL News: A Cross-lingual News Aggregator and Reader - Belyaeva, Evgenia; Berčič, Jan; Bercic, Katja; Fuart, Flavio; Košmerlj, Aljaž; Muhič, Andrej; Rehar, Aljoša; Rupnik, Jan; Trampuš, Mitja (SPRINGER INT PUBLISHING AG, GEWERBESTRASSE 11, CHAM, CH-6330, SWITZERLAND, 2015)
We present 3XL News, a multi-lingual news aggregation application for iPad that provides real-time, comprehensive, global and multilingual news coverage. Using methods, developed within the XLike project, for semantic data extraction from news articles and linking of news stories we are able to construct a concise, yet in-depth view of current news stories and their semantic relation. This enables users real-time monitoring of current global events and analysis of diverse reporting in different languages and navigation across related news stories.

(Deep) FAIR mathematics - Bercic, Katja; Kohlhase, Michael; Rabe, Florian (it - Information Technology, 2020)
In this article, we analyze the state of research data in mathematics. We find that while the mathematical community embraces the notion of open data, the FAIR principles are not yet sufficiently realized. Indeed, we claim that the case of mathematical data is special, since the objects of interest are abstract (all properties can be known) and complex (they have a rich inner structure that must be represented). We present a novel classification of mathematical data and derive an extended set of FAIR requirements, which accomodate the special needs of math datasets. We summarize these as deep FAIR. Finally, we show a prototypical system infrastructure, which can realize deep FAIRness for one category (tabular data) of mathematical datasets.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Accessible; deep FAIR; Findable; Interoperable; Mathematical Data; Reusable

DiscreteZOO: A Fingerprint Database of Discrete Objects - Bercic, Katja; Vidali, Janoš (Mathematics in Computer Science, 2020)
In this paper, we present DiscreteZOO, a project which illustrates some of the possibilities for computer-supported management of collections of finite combinatorial (discrete) objects, in particular graphs with a high degree of symmetry. DiscreteZOO encompasses a data repository, a website and a SageMath Package.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Fingerprint database; Maniplexes; SageMath package; Vertex-transitive graphs; Website

DiscreteZOO: Towards a Fingerprint Database of Discrete Objects - Bercic, Katja; Vidali, Janoš (ICMS, 2018)
There have been various efforts to collect certain mathematical results into searchable databases. In this paper, we present DiscreteZOO: a repository and a fingerprint database for discrete mathematical objects. At the moment, it hosts collections of vertex-transitive graphs and maniplexes, which are a common generalisation of maps and abstract polytopes. The project encompasses a tool for handling and maintaining collections of objects, as well as a website and SageMath package for interacting with the database. The project aims to become a general platform to make collections of mathematical objects easier to publish and access.
Keywords: Fingerprint database; Vertex-transitive graphs; Maniplexes; SageMath package; Website

Supporting Data-Driven Mathematics: Database and Interface Generation - Bercic, Katja (FPSAC 2019 - 31st International Conference on Formal Power Series and Algebraic Combinatorics, 2019)
Easier access to computation is turning mathematics into an at least a partially data-driven discipline. But it does not use the tools of the data trade: a majority of datasets are still shared in an ad hoc manner. We contribute an automated database setup process which builds a complete website stack, from the database schema to a web interface, from a dataset declaration.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Database framework; Mathematical data; Schema declaration

Supporting Data-Driven Mathematics: Database and Interface Generation - Bercic, Katja (Seminaire Lotharingien de Combinatoire, 2019)
Easier access to computation is turning mathematics into an at least a partially data-driven discipline. But it does not use the tools of the data trade: a majority of datasets are still shared in an ad hoc manner. We contribute an automated database setup process which builds a complete website stack, from the database schema to a web interface, from a dataset declaration
CRIS-Team Scopus Importer:2024-12-16
Keywords: database framework; mathematical data; schema declaration

Tetravalent arc-transitive graphs of order twice a product of two primes - Bercic, Katja; Ghasemi, Mohsen (Discrete Mathematics, 2012)
In this article a complete classification of tetravalent arc-transitive graphs of order twice a product of two primes is given. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arc-transitive graphs; Symmetric graphs; Cayley graphs

Towards a heterogeneous query language for mathematical knowledge - Bercic, Katja; Kohlhase, Michael; Rabe, Florian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
With more than 120.000 articles published annually in mathematical journals alone, mathematical search has often been touted as a killer application of computer-supported mathematics. But the artefacts of mathematics – e.g. mathematical documents, formulas, examples, algorithms, concrete data sets, or semantic web-style graph abstractions – that should be searched cover a variety of aspects. All are organized in complex ways and offer distinct challenges and techniques for search. Existing representation languages, the corresponding query languages and search systems usually concentrate on only one of these aspects. As a consequence, each system only partially covers the information retrieval needs of mathematical practitioners, and integrated solutions allowing multi-aspect queries are rare and basic. We present an architecture for a generic multi-aspect search system and analyze the requirements on paradigmatic practical information retrieval needs.
CRIS-Team Scopus Importer:2020-11-06

Towards a Unified Mathematical Data Infrastructure: Database and Interface Generation - Bercic, Katja; Kohlhase, Michael; Rabe, Florian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
Data plays an increasing role in applied and even pure mathematics: datasets of concrete mathematical objects proliferate and increase in size, reaching upÂ to 1Â TB of uncompressed data and millions of objects. Most of the datasets, especially the many smaller ones, are maintained and shared in an ad hoc manner. This approach, while easy to implement, suffers from scalability and sustainability problems as well as a lack of interoperability both among datasets and with computation systems. In this paper we present another substantial step towards a unified infrastructure for mathematical data: a storage and sharing system with math-level APIs and UIs that makes the various collections findable, accessible, interoperable, and re-usable. Concretely, we provide a high-level data description framework from which database infrastructure and user interfaces can be generated automatically. We instantiate this infrastructure with several datasets previously collected by mathematicians. The infrastructure makes it relatively easy to add new datasets.
CRIS-Team Scopus Importer:2019-07-26

Two-arc-transitive two-valent digraphs of certain orders - Bercic, Katja; Potočnik, Primož (Ars Mathematica Contemporanea, 2016)
The topic of this paper is digraphs of in-valence and out-valence 2 that admit a 2-arctransitive group of automorphisms. We classify such digraphs that satisfy certain additional conditions on their order. In particular, a classification of those with order kp or kp(2) where k <= 14 and p is a prime can be deduced from the results of this paper.
Keywords: Graph; digraph; arc-transitive; order